The effect of microsurgery inguinal varicocelectomy by secondary infertile male patients with clinical varicocele - Badur, N.; Karakeci, A.; Cayan, S.; Orhan, I. (Oxford Univ Press, 2015)
[Abstract Not Available]
31st Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUN 14-17, 2015 -- Lisbon, PORTUGAL
Keywords: varicocele; secondary infertility; microsurgery inguinal varicocelectomy